1999
DOI: 10.1111/j.1365-2141.1999.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the administration of recombinant hirudin and/or tissue‐plasminogen activator (t‐PA) on endotoxin‐induced disseminated intravascular coagulation model in rabbits

Abstract: Summary.We evaluated the effect of r-hirudin and/or tissueplasminogen activator (t-PA) in a model of DIC in rabbits induced by i.v. infusion of 100 mg/kg/h/6 h endotoxin. Rabbits were treated with saline (endotoxin control group), r-hirudin at 0·3 mg/kg/h/6 h, t-PA at 0·3 mg/kg for 90 min and r-hirudin plus t-PA at the doses described above. The best results were achieved when r-hirudin and t-PA were infused together. This treatment reduced the consumption of platelets and protein C and attenuated the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…The prolongation of APTT and PT after administration of LPS was significantly prevented by treatment with PTX. In harmony with earlier findings (Paloma et al, 1992;Munoz et al, 1999;Hermida et al, 1999;Montes et al, 2000), the injection of endotoxin into the rabbits caused a significant decrease in fibrinogen concentration at 6 h in the present investigation. Low fibrinogen level can be due to impaired fibrinogen synthesis as a result of hepatic tissue damage, increased consumption during DIC, loss into the extravascular spaces and massive haemorrhage.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The prolongation of APTT and PT after administration of LPS was significantly prevented by treatment with PTX. In harmony with earlier findings (Paloma et al, 1992;Munoz et al, 1999;Hermida et al, 1999;Montes et al, 2000), the injection of endotoxin into the rabbits caused a significant decrease in fibrinogen concentration at 6 h in the present investigation. Low fibrinogen level can be due to impaired fibrinogen synthesis as a result of hepatic tissue damage, increased consumption during DIC, loss into the extravascular spaces and massive haemorrhage.…”
Section: Discussionsupporting
confidence: 93%
“…Some authors have reported that low levels of AT-III are associated with a higher mortality in septic shock (Fourrier et al, 1993). LPS given alone reduced the AT-III activity, which is in agreement with previous reports (Scherer et al, 1995;Munoz et al, 1999;Hermida et al, 1999;Yamazaki et al, 1999;Asakura et al, 2001). The simultaneous administration of PTX to endotoxin-treated rabbits did not prevent the decrease in AT-III activity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations